The lessons of things to the cultural mediation: attitudinal permanencies and possibilities of dissent and countervisuality in History museum education - Alencar, Valeria Peixoto de [UNESP] (Assoc Servidores Arquivo Nacional, 2016)
This article was based on the thesis Cultural mediation in history museums and exhibitions. Conversations about images/history and their interpretation (ALENCAR, 2015) and presents some issues about the imaginary that involves history museums and exhibitions and possible processes at educational work in these museums. It will be discussed a few questions about intuitive method of teaching. the lessons of things., the methodology of the Heritage Education and pointing the proposals of the cultural mediation as potency in the provocation of dissent (RANCIERE, 2014) and countervisuality (MIRZOEFF, 2011).
Keywords: Museum education; dissent; countervisuality